SNACKABLE CONTENT CREATION IN THE DIGITAL AGE: A CASE STUDY OF SOCIAL MEDIA CONTENT PRODUCTION AT NET TV - Ferdinandus, Dinda Deva; Alvin, Silvanus (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study explores the effective utilization of social media to promote TV programmes, specifically focusing on NET Mediatama Televisi (Net TV) in Indonesia. The COVID-19 pandemic has led to an increase in social media usage, making it an ideal platform to promote TV programmes. The case study design was used, and data was collected through observation and physical artifacts. The analysis identified that NET TV encourages content creators to create snackable and interactive content to promote their programmes effectively. This study highlights the importance of social media in promoting TV programmes and the need for media companies to adapt to changing audience behavior.